ATRP synthesis of polyallene-based amphiphilic triblock copolymer. Issue 45 (7th November 2017) - Ding, Aishun; Lu, Guolin; Guo, Hao; Huang, Xiaoyu
Abstract : This article reports the synthesis of a new amphiphilic double-bond-containing ABA triblock copolymer by a combination of free radical polymerization and ATRP. Abstract : A series of ABA triblock copolymers, comprising double-bond-containing poly(phenoxyallene) (PPOA) and poly(methoxymethyl methacrylate) (PMOMMA) segments, was synthesized by a combination of conventional free radical polymerization, atom transfer radical polymerization (ATRP) and the site transformation strategy. A new bifunctional initiator containing azo and Br-containing ATRP initiating groups was employed to initiate the conventional free radical homopolymerization of phenoxyallene with a cumulated double bond to give a PPOA-based macroinitiator (Br-PPOA-Br) bearing ATRP initiating groups at both ends. Next, ATRP of MOMMA was initiated by Br-PPOA-Br macroinitiator to produce PMOMMA- b -PPOA- b -PMOMMA triblock copolymers, which were subsequently hydrolyzed to afford PMAA- b -PPOA- b -PMAA amphiphilic triblock copolymers. The critical micelle concentration (cmc) of PMAA- b -PPOA- b -PMAA amphiphilic triblock copolymer in aqueous solution was determined by fluorescence probe technique and the dependence of cmc on pH was also investigated. These amphiphilic triblock copolymers self-assembled into wormlike and large compound micelles in aqueous media.